Kompetensi Pedagogik Guru dalam Pendidikan Islam Perspektif Tafsir Al Quran - Asswan Cahyadi, Wendy; Qomariyah, Siti Qomariyah (LP. Ma'arif Janggan Magetan, 2022)
Indonesia is still a country with a low quality of education. The low quality of education in Indonesia can be caused by poor infrastructure and teacher competence. The purpose of this study was to determine the pedagogical competence of teachers in Islamic education from the perspective of Al-Qur'an interpretation. This research is library research, with descriptive method of qualitative analysis. The researcher describes the Teacher's Pedagogic Competence in Islamic Education, then analyzes it in detail and depth with the Al-Qur'an Tafsir Perspective. Namely the book Tanwir Miqbas Min Tafsir Ibn Abbas, Tafsir Jalalain, Tafsir al Qur'an al Azim. Research results: research results include: 1. Understanding of students; Effective Communication (qaulan balighah/words that leave scars and qaulan makrufah/good words) 2. Objectives of Islamic education; 3. Obligation to seek knowledge; 4. Curriculum 5. Evaluation 6. Learning Models and Methods: Uswatun Hasanah (Good Exemplary) Method, Teaching to be Thorough, Detailed and Responsible, Lecture Method with Wisdom and Mauidlah Hasanah, Collaborative Discussion Learning Method with Creative Thinking, Story Method / Story, Method of Approaching Imagery as Lesson, Method of Reward / Targhib / Reward and Punishment / Tarhib / Punishment, Method of Reading, Studying and Studying with Basmalah and memorization method.